Cathodal Transcranial Direct Current Stimulation in Acute Ischemic Stroke: Pilot Randomized Controlled Trial. Issue 6 (19th April 2021) - Pruvost-Robieux, Estelle; Benzakoun, Joseph; Turc, Guillaume; Marchi, Angela; Mancusi, Rossella Letizia; Lamy, Catherine; Domigo, Valérie; Oppenheim, Catherine; Calvet, David; Baron, Jean-Claude; Mas, Jean-Louis; Gavaret, Martine
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: In acute stroke, preventing infarct growth until complete recanalization occurs is a promising approach as an adjunct to reperfusion therapies to reduce infarct size and improve outcome. In rodent models, cathodal transcranial direct current stimulation (C-tDCS) decreases peri-infarct depolarizations and reduces infarct volume. We hypothesized that C-tDCS would nonpharmacologically reduce infarct growth in hyperacute middle cerebral artery territory stroke patients receiving reperfusion therapy. Methods: STICA (Cathodal Transcranial Direct Stimulation in Acute Middle Cerebral Artery Stroke) was a pilot single-center, double-blind, 2-arms 1:1 randomized trial evaluating the safety, feasibility, and efficacy of C-tDCS versus sham stimulation in patients eligible for recanalization therapies. Magnetic resonance imaging was obtained both on admission and 24 hours later. The primary end point was 24-hour infarct growth. Secondary outcomes were (1) National Institutes of Health Stroke Scale score difference between day 7 and admission and (2) 3-month modified Rankin Scale score. Results: Forty-five patients were randomized. Median magnetic resonance imaging-to-C-tDCS start time was 45 minutes; C-tDCS was started before completion of recanalization procedure in all patients. The intervention proved feasible in all patients. No major adverse effects occurred in either group. There was no significant difference between active and sham groups for any end point. However, an apparent trend towards smaller infarct growth in the C-tDCS arm was observed in the whole group (unadjusted median difference [IC95% ]: −2.2 mL [−12.2 to 1.5]) and in the prespecified subsamples with moderate-to-severe stroke and large vessel occlusion (−5.7 mL [−21.6 to 2.6] and −7.7 mL [−24.2 to 2.6], respectively). Conclusions: C-tDCS was feasible and well tolerated. No significant difference was found between the active and sham groups. However, the data suggest potential benefits of C-tDCS in patients with National Institutes of Health Stroke Scale score of >10 or large vessel occlusion. Using the observed effect size and standard α=5% and β=20%, samples of 102 and 86, respectively, can be estimated for future trials in patients with these characteristics. Randomized trials particularly targeting these populations may be warranted.